Analisis Kesulitan Siswa dalam Menyelesaikan Soal Matematika Kelas V Sekolah Dasar - Akmal Rijal (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2021)
This study aims to determine the types of mistakes as well as the causative factors to this mistakes, of the fifth grade elementary school students in solving problemson fraction. The research applies a qualitative descriptive method. The research subjects taken were 28 grade 5 students at 55 Lubuklinggau public elementary school. The data were collected using the techniques of interview observation, questions and documentation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results show that the types of mistakesexperienced by students in solving mathematical problem were (1) factual errors, in which students assume that studying fraction is hard since it will face with lots of mathematical calculations operation that is difficult to understand. (2) students did not understand the essence of the mathematical problem, as a result they did not grasp the way to solve it. (3) students understand the formula but could not write the steps in solving the problem, and (4) students can not solve the problem correctly in terms of calculating addition, subtraction, and division operations. The factors causing mistakes in solving mathematical problems are (1) student’s internal factor, it is their low interest, (2) external factor, like the family environment which is less helpful in learning fraction.